Effects of Shifting Class Schedule on the Academic Performance of Grade 12 Students - Marino, Sharmine (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of shifting class schedules on the academic performance of Grade 12 students in selected senior high schools in the Division of Rizal during the School Year 2025–2026. Specifically, it included students from Cainta Senior High School, Cardona Senior High School, Morong National Senior High School, and Tanay Senior High School. Employing a descriptive survey research design and documentary analysis, the study utilized a researcher-made questionnaire to assess the perceived effects of shifting schedules in terms of time allocation, student preparedness, and student engagement. Academic performance was measured using students’ first-quarter grades.A total of 359 respondents were selected from a population of 3,515 students using Slovin’s formula and stratified sampling. The respondents were profiled according to age, sex, sibling position, family size, parents’ educational attainment and occupation, monthly family income, and class schedule. Findings revealed that most respondents were 17-year-old females, commonly first or second-born, from low-income families with parents who are high school graduates.Results indicated that shifting class schedules have a high perceived effect on academic performance across time allocation, preparedness, and engagement. However, no significant relationship was found between the perceived effects and actual academic performance, which was generally rated as very satisfactory. Additionally, no significant differences were observed across most profile variables, except for monthly family income, which showed a significant difference in relation to student engagement.The study concludes that while shifting schedules influence students’ learning experiences, they do not significantly affect academic outcomes. It is recommended that schools enhance time management strategies, improve instructional delivery, and strengthen teacher collaboration to address scheduling challenges. Further experimental studies are also encouraged to validate the effectiveness of double-shift class systems
Keywords: shifting class schedule, academic performance, student engagement, time allocation, student preparedness, senior high school, descriptive survey, Philippines